A design synthesis for steel-hulled trawlers - Vea, Reynaldo B.
A computer aided concept design synthesis for trawlers is developed. Hull resistance is estimated from a previously published statistical analysis of trawler resistance data. Construction costs are likewise approximated from published graphs, after updating where necessary. Extensive curve fitting was done to make these existing information suitable for a computerized procedure. A numerical example relevant to Philippine conditions is given.